2008
DOI: 10.1111/j.1751-0813.2007.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination of feral pigs (Sus scrofa) using iophenoxic acid as a simulated vaccine

Abstract: Objectives  To develop an encapsulation method for delivery of vaccines to feral pigs, and quantify the effect of iophenoxic acid on captive feral pig blood iodine concentrations to assist in investigation of factors affecting vaccine uptake.Design and methods  Feral pigs were administered iophenoxic acid by oral gavage, and consumption was assessed for different encapsulation methods in baits. Blood iodine concentrations were monitored for eight days after consumption. The relationship between dose rate, time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 17 publications
0
18
0
Order By: Relevance
“…This confirmed that encapsulated liquids can be delivered to wild boar within baits, and the vaccine would eventually come to contact with the oral mucosa. Nonetheless, although eating or chewing a vaccine capsule is a primary requirement, this may not necessarily result in the actual vaccination occurring (Cowled et al 2008); this needs to be assessed under experimental and field conditions. Placing the baits inside selective feeders for wild boar piglets was found to be a much more selective method for delivering oral vaccines to wild boar because only young wild boar visited the feeders by night.…”
Section: Discussionmentioning
confidence: 99%
“…This confirmed that encapsulated liquids can be delivered to wild boar within baits, and the vaccine would eventually come to contact with the oral mucosa. Nonetheless, although eating or chewing a vaccine capsule is a primary requirement, this may not necessarily result in the actual vaccination occurring (Cowled et al 2008); this needs to be assessed under experimental and field conditions. Placing the baits inside selective feeders for wild boar piglets was found to be a much more selective method for delivering oral vaccines to wild boar because only young wild boar visited the feeders by night.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty milligrams of IPA per bait may be insufficient to detect bait consumption in adult animals or when they consume one bait only (Cowled et al 2008). Therefore, higher amounts of IPA (40 mg/bait) as used herein may give more reliable estimations of bait uptake (Cowled et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Et-IPA has been used successfully to investigate wild boar baits and baiting strategies to deliver oral vaccines, contraceptives, and toxicants (Fletcher et al 1990;Mitchell 1998;Fleming et al 2000;Campbell et al 2006;Cowled et al 2008;Massei et al 2009). Et-IPA can be incorporated into baits as a chemical marker because it binds to proteins in the blood plasma and elevates the protein-bound iodine in animals that consume Et-IPA-marked baits.…”
Section: Introductionmentioning
confidence: 99%
“…The latter indicates that vaccination with baits before that age is probably not possible. In order to follow and study oral uptake of the baits, iophenoxic acid has been successfully used as biomarker (Cowled et al, 2008).…”
Section: Wild Boarmentioning
confidence: 99%